Kinerja Pegawai Negeri Sipil Di Kantor Kecamatan Sario Kota Manado - Sumual, Maervilli; Liando, Daud; Rares, Joyce (JURNAL ILMIAH SOCIETY, 2016)
Performance is the result of the quality and quantity of work accomplished by an employee in carrying out their duties in accordance with the responsibilities given to him. Performance is affected by factors such as ability and motivation. This study aims to determine the performance of civil servants in the Sario District Office of Manado City. The methodology used for this study is qualitative research methods. The data is collected through direct interviews and field observations. The results showed that the performance of civil servants in the Sario District Office of Manado City is not maximized. This is caused by various level of workability, there’s also lack of motivation, financial or non-financial one, given by the employer. Keywords : Performance, ability, motivation